Source water microorganism assessment in three cities in China: A comparative study - Liu, Yang; Smith, Charlotte D.; Li, Hongxing; Wang, Duochun (Frontiers in Environmental Science, 2022)
Reservoirs, rivers and groundwater are the top three sources of drinking water supplies in China. As microbial contamination of drinking water is still a prominent water quality problem in rural areas, understanding the microbial quality of these sources is important to the public’s health and economic prosperity of communities. In this study, three types of source water samples were collected from three cities in China. Bacterial contamination indicators testing showed that, total coliforms (TCs) and E. coli were not detected in groundwater, but both were detected in river and reservoir water. Total bacteria (TB) of rivers and Res-Ⅰ were greater than 100 CFU/ml, while less than 100 CFU/ml from Res-Ⅱ and groundwater. By selective culture of pathogenic microorganisms, Salmonella spp. were isolated from river water and no pathogenic microorganisms were isolated from the other two types of water sources. Further analysis by 16S rRNA gene amplicon sequencing indicated that, there were 14,114 operational taxonomic unit (OTU) of microbial abundance from all 30 samples, and most OTUs were present in river water (15.17%), reservoir water (10.46%) or groundwater (43.91%), while 1,508 OTUs (10.68%) were shared by all three types of water sources. There were significant differences in the microbial communities of the three types of source water (p<0.05). Based on the Ace, Chao, Shannon-Weaver, and Simpson indices, the species diversity of bacteria in groundwater was higher than in river water or reservoir water (p<0.05), with the reservoir water having the lowest diversity of bacteria. More than seven potential pathogenic bacteria were detected in 30 water samples, for example, E. coli, Staphylococcus aureus, Clostridioides difficile and Bacteroides fragilis were present in all three types of water sources, while other pathogenic bacteria occurred only in some of the water samples. Clostridium perfringens were detected in river water and groundwater. This study revealed the diversity of microorganisms in three different type of source water, and identified the presence of pathogenic microorganisms. Furthermore, we illustrated how 16S rRNA gene amplicon sequencing could be used as a supplementary technology to provide valuable information for monitoring of water sources and water supply systems.